Sonata quasi una fantasia : Oeuv. 27 no. [2] composée pour le piano-forte par L. van Beethoven - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Jean Aug. Böhme; Hamburg; Germany, 2022)
Edition of the Piano Sonata no. 14 in C# minor, op. 27, no. 2, published in an unnamed series by Jean Aug. Böhme in Hamburg. With decorative passé-partout title page. Plate number 165-2.